2021
DOI: 10.3324/haematol.2021.278295
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical unloading aggravates bone destruction and tumor expansion in myeloma

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Treatment with 5Z-7 at 20 mg/kg twice a week has been reported to reduce MM growth enhancement in immobilized hind legs [ 6 ]. 5Z-7 at 20 mg/kg every other day for 14 days has been shown in vivo to suppress MM tumour growth, serum IgG2b levels, and bone destruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with 5Z-7 at 20 mg/kg twice a week has been reported to reduce MM growth enhancement in immobilized hind legs [ 6 ]. 5Z-7 at 20 mg/kg every other day for 14 days has been shown in vivo to suppress MM tumour growth, serum IgG2b levels, and bone destruction.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is of critical importance in the pathogenesis of MM [ 5 ]. Targeting TAK1 has recently gained attention as a possible antimyeloma strategy [ 6 8 ]. We have previously shown that TAK1-inhibitors are cytotoxic to human myeloma cell lines patient cells [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, MM tumor growth was suppressed in mice that underwent mechanical loading compared with control mice. We conducted an experiment with mechanical unloading in MM-bearing mice [ 65 ]. Right hind legs of mice were immobilized and exposed to mechanical unloading by sciatic denervation or casting with an adhesive bandage.…”
Section: Mutual Interaction Between MM Cells and Bone Microenvironmentmentioning
confidence: 99%